High Neutrophil-to-Platelet Ratio Is Associated With Hemorrhagic Transformation in Patients With Acute Ischemic Stroke - He, Weilei; Ruan, Yiting; Yuan, Chengxiang; Cheng, Qianqian; Cheng, Haoran; Zeng, Yaying; Chen, Yunbin; Huang, Guiqian; Chen, Huijun; He, Jincai (Frontiers in Neurology, 2019)
Background: Hemorrhagic transformation (HT) is a complication that may cause neurological deterioration in patients with acute ischemic stroke. Both neutrophil and platelet have been associated with the stroke progression. The aim of this study was to explore the relationship between neutrophil-to-platelet ratio (NPR) and HT after acute ischemic stroke. Methods: A total of 279 stroke patients with HT were consecutively recruited. HT was diagnosed using magnetic resonance imaging (MRI) or computed tomography (CT) and classified into hemorrhagic infarction (HI) and parenchymal hematoma (PH). Blood samples for neutrophil and platelet counts were obtained at admission. Meanwhile, 270 age- and gender-matched controls without HT were included for comparison. Results: Among the patients with HT, 131 patients had PH and 148 patients had HI. NPR was higher in patients with PH than those with HI or non-HT (36.8 (23.7-49.2) vs. 26.6 (17.9-38.3) vs. 19.1 (14.8-24.8), P < 0.001). After adjustment for potential confounders, high NPR remained independently associated with the increased risk of HT (OR = 2.000, 95% CI: 1.041-3.843, P = 0.037). NPR (>39.9) was independently associated with PH (OR = 2.641, 95% CI: 1.308-5.342, P = 0.007). Conclusions: High NPR was associated with the increased risk of HT especially PH in patients with acute ischemic stroke.